Skema Aktan Greimas pada Kisah Umar dalam Kitab Arabiyah Linnasyiin Jilid 4 - Dian Azizah; Nursukma Suri; Natasya Ilza; Layla Hanum (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2026)
This study analyzes Greimas’s actant scheme in the story of Umar bin Khattab in Arabiyah Linnasyiin Volume 4, pages 44–45. The purpose of this study is to describe the actant structure and explain the function of each actant in building the narrative meaning of the story. This study uses a descriptive qualitative approach with narrative analysis of the Arabic text accompanied by Indonesian translation. The findings show that the story contains three main actant schemes: Umar’s hijrah from Mecca to Medina, Umar’s role as a caliph who monitors the condition of his people, and Umar’s assistance to a poor woman and her children. In these episodes, Umar appears as the main subject driven by courage, responsibility, care, and justice. The actant scheme shows that sender, object, receiver, helper, and opposant play important roles in constructing Umar’s leadership as a model figure. This study confirms that A.J. Greimas’s actant model is effective for reading Islamic narrative texts and also has pedagogical implications for Arabic language learning based on narrative texts.